Revision of Condyloderes (Kinorhyncha, Cyclorhagida) including description of Condyloderes shirleyi sp. nov. - Neuhaus, Birger; Zotto, Matteo Dal; Yamasaki, Hiroshi; Higgins, Robert P. (Zootaxa, 2019)
The description of a new representative of the species-poor genus Condyloderes Higgins, 1969 from the Northeast Pacific (Alaska) is reported. The analyzed specimens of Condyloderes shirleyi sp. nov. showed a significant variation of numerous morphological characters, along with female-specific traits known also from other congeneric species. These findings stimulated the re-investigation of the type material of the six species of Condyloderes described so far, i.e., C. kurilensis Adrianov & Maiorova, 2016, C. megastigma Sørensen, Rho & Kim, 2010b, C. multispinosus (McIntyre, 1962) Higgins, 1969, C. paradoxus Higgins, 1969, C. setoensis Adrianov, Murakami & Shirayama, 2002, and C. storchi Higgins, 2004 in Martorelli & Higgins, 2004. Our study allowed to reveal various morphological novelties and to emend the diagnosis of these species and of the genus Condyloderes. Furthermore, our analysis led to synonymize C. megastigma with C. setoensis. The results of our investigation about the significant variation in C. shirleyi sp. nov. raise a wider question on species identity within Kinorhyncha, underscoring the necessity, if possible, to describe new species from a higher number of specimens and to concentrate on the morphological variation of the going-to-be-described species.